Beyond buttons: repurposing of casein-based materials in education and industry—a review - Carlo Santulli (Academia Materials Science)
The development of casein-based plastics, as well as starch-based ones, produced from hydrocarbons and their derivatives is an alternative to conventional plastics. While its use dates to the late 19th century under the principal name of galalith, interest on casein-based plastics has revived recently due to increasing efforts for implementing circular economy and converting waste to reusable materials. The abundance of waste derived from the dairy industry allowed casein to enter the field of material tinkering for design process. In the past two decades, extensive research has been carried out, in a more industrial sense, on the revival of casein-based materials, mostly, but not exclusively, for the production of formaldehyde-free products. In these studies, research focused particularly on the creation of packaging films, in some cases edible ones, and experiments were conducted on the effect of blending starch or pectins with different plasticizers, such as polyols (e.g., glycerol and sorbitol). Other applications of casein were also further explored such as the biomedical use of casein films, especially in wound dressing, and the use of casein in the production of fibers for textile and antibacterial purposes. In general, studies conducted on casein materials have shown considerable promise to replace the use of oil-based plastics or to serve as the matrix for natural fiber composites.